Analysis of e-learning user satisfaction at XYZ University in the new normal era of the covid-19 pandemic - Rudy Hartono; Muhammad Zarlis (Jurnal Mantik, 2023)
In 2020 Indonesia implemented a new normal policy as a form of adaptation to the Covid-19 pandemic. In the new normal period, XYZ university uses e-learning as one of the distance learning media to deliver learning materials to students. This study aims to analyze the factors that affect student satisfaction in using e-learning. The End-User Computing Satisfaction (EUCS) model is used as a research model. The data was taken through the dissemination of questionnaires using google from 249 respondents consisting of students from three study programs. From the data obtained, analysis was carried out using the Structural Equation Model (SEM) with SmartPLS software. The results showed that the Content, Ease of Use, and Timeliness variables had a positive and significant effect on User Satisfaction while the Accuracy and Format variables did not have a significant effect on User Satisfaction